An automated mini buffy coat preparation method for use in mini extracorporeal photopheresis treatment of graft‐vs‐host‐disease in a low body weight pediatric patient. Issue 4 (4th March 2019) - Matic, Toni; Bojanic, Ines; Mazic, Sanja; Golubic Cepulic, Branka; Bilic, Ernest
Abstract: A mini extracorporeal photopheresis (mini‐ECP) "off line" technique has been developed for use in the treatment of small children and patients with apheresis contraindications. Until now various methods have been used for buffy coat separation from whole blood. In this report we describe a protocol for mini buffy coat preparation using the automated Sepax laboratory separator for "off line" ECP treatment in a low body weight child with graft‐vs‐host‐disease. According to our results this alternative method has been proven feasible and tolerable.